2003
DOI: 10.1159/000071082
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of alpha-2-Heremans-Schmid Glycoprotein in CSF of Patients with Low-Grade Gliomas

Abstract: Little is known about the expression of mitogens and other tumour-related substances in the cerebrospinal fluid (CSF) of glioma patients. The aim of the current study was to determine the presence of aberrant proteins in the CSF of patients with low-grade gliomas. Lumbar puncture was performed in 8 adult patients with supratentorial low-grade gliomas at the time of diagnosis and in 7 controls. Two-dimensional gel electrophoresis and matrix-assisted laser desorption/ionisation time of flight mass spectrometry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…In contrast to the risks associated with CSF collection, serum is safely and easily obtainable with no risk to patients or normal subjects. A previous study reported increased AHSG in the CSF of patients with low-grade gliomas (27 ), who were found to have re-duced serum AHSG in our study. AHSG immunohistochemistry (not shown) revealed AHSG leakage from the blood through disrupted blood-tumor barrier into the CSF in glioma patients, thus explaining the reported increase in CSF AHSG.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast to the risks associated with CSF collection, serum is safely and easily obtainable with no risk to patients or normal subjects. A previous study reported increased AHSG in the CSF of patients with low-grade gliomas (27 ), who were found to have re-duced serum AHSG in our study. AHSG immunohistochemistry (not shown) revealed AHSG leakage from the blood through disrupted blood-tumor barrier into the CSF in glioma patients, thus explaining the reported increase in CSF AHSG.…”
Section: Discussionsupporting
confidence: 79%
“…More importantly, this protein inhibits intestinal tumor progression by antagonistic action against transforming growth factor ␤ [50]. However, conversely, an earlier proteomic study detected higher levels of two isoforms of AHSG in patients with lowgrade gliomas compared with a control group consisting of patients with mixed neurological diagnoses [51]. For the first time, we detected increased plasma levels of AHSG in CRC patients compared to patients with adenomas.…”
Section: Discussionmentioning
confidence: 46%
“…Two isoforms of A2HSG were expressed at higher levels in patients with low-grade gliomas compared with the control group consisting of patients with mixed neurological diagnoses. In one patient, the level of AHSG was significantly reduced after gross total resection of the tumor [355]. Two tumor-related proteins, N-myc oncoprotein and low-molecular weight caldesmon, were identified in CSF samples of patients with primary brain tumors [356].…”
Section: Application To Neurological Disease Detectionmentioning
confidence: 97%